The Use of Interactive Techniques, Role-Playing Games, and Dramatization to Increase Linguistic Creativity and Motivation of Students - Biynazarova, Nazgul; Abdimomunova, Apal; Dzhilkibaeva, Nurizad; Takenova, Zhyldyz; Asanova, Dinara (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
The study was conducted to identify relevant interactive methods of teaching English. For this purpose, a survey of the level of motivation to language learning was conducted, which included a pedagogical experiment with 46 students of 7 grades of the public school “Taalim”. The results of questionnaire survey of students and observation revealed a qualitative positive growth of linguistic creativity and motivation to learn English, due to the use of role-playing games and theatrical performances in lessons. To investigate the use of interactive techniques in English language teaching and to share experiences with colleagues, a conversation was held with 23 teachers, including undergraduates using these methods. The paper examines the concepts of motivation, play, dramatization, describes the main types and methods of using interactive techniques in teaching. It was determined that games and dramatization play an important role in learning. The use of role-playing games promotes language learning, helps to increase cognitive interest in the subject, while making the learning process less difficult, develops memory and thinking, focuses attention on a particular subject, and motivates students to learn English. Dramatization technologies develop imagination, contribute to the automatic understanding of rhymed language phrases, and the development of the student’s sensory and emotional sphere. The conducted research highlighted the main features of the use of game techniques in the process of teaching English and argued that it is important to introduce games and dramatization into the learning process. Interactive methods imply the interest of students in mastering a foreign language, the desire to perceive a foreign language and learn to speak a foreign language. Linguistic creativity and motivation are enhanced through role-playing and dramatization, enabling children to overcome the language barrier and increase their own self-esteem.